EKSPLORASI KONSORSIUM PBRM (PLANT BENEFICIAL RHIZOSPHERIC MICROORGANISM) DALAM NUE (NUTRIENT USE EFFICIENCY) PADA PERTUMBUHAN JAGUNG (Zea mays L) - Agung Setya Wibowo; Intan Fuji Arriani; Palupi Puspitorini; Nyonita Punjungsari, Tyas (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2019)
PBRM (Plant Beneficial Rhizospheric Microorganism) is a microbe that is able to form colonies in plant roots (rhizosphere) that have the ability to fix nitrogen (N), and dissolve potassium (K), phosphorus (P), and zinc (Zn). Increasing NUE can increase plant growth through various mechanisms. Population and dynamics of rhizosphere microorganisms are different from other soil microorganisms, this is caused by an increase. The purpose of this study was to determine the type of rhizosphere bacteria that can be as PBRM. The method used The research was conducted at the Microbiology Laboratory of the Faculty of Agriculture, Brawijaya University, Malang. The characterization process was carried out in UB's microbiology laboratory. 50 grams of soil for planting corn were put into an erlenmeyer containing 500 ml NB (for bacteria) and 500 ml liquid PDA (for mold) and then incubated with the secretary for about 24 hours and then diluted in series to a dilution rate of 10-3,10-4,10 -5. Then from the dilution factor of 10-3,10-4,10-5 0.1 ml is taken and inoculated in solid media by the pour plate method. The results showed that the antagonistic rhizosphere bacteria were P. fluorescens, B. subtillis, and Rhizobium sp.